Junior-to-senior transition in elite female football: identifying predominant sources of stress among junior players from both player and coach perspectives - Selbekk, S.; Lilleengen, M.; Stålesen, J.; Ransom, D.; Sæther, S. (Frontiers in Psychology, 2025)
Introduction: The purpose of this case study is to gain insight into and a deeper understanding of the predominant sources of stress during the junior-to-senior transition experienced by current and former female junior players and their male coaches from both the junior and senior teams.